A Generalized q-Gruss Inequality Involving the Riemann-Liouville Fractional q-Integrals - Secer, Aydin; Purohit, S. D.; Selvakumaran, K. A.; Bayram, Mustafa (HINDAWI LTD, 2014)
The aim of this paper is to establish q-extension of the Gruss type integral inequality related to the integrable functions whose bounds are four integrable functions, involving Riemann-Liouville fractional q-integral operators. The results given earlier by Zhu et al. (2012) and Tariboon et al. (2014) follow the special cases of our findings.
Keywords: Mathematics